THE INFLUENCE OF PERCEPTUAL FEATURES (SHAPE, COLOUR, AND SIZE) IN THE STAGE IV (A NO-B) ERROR - Carranza Carnicero, José Antonio (Anales de Psicología / Annals of Psychology)
It was investigated whether the perceptual features (shape, color and size) of hiding places affected the performance in the search task of Stage IV of the object permanence. 15 infants allocated in the Stage IV of the sensoriomotor period were used. Afterwards, the subjects were given five trials for every variable manipulated (shape, color, and size). The results indicate that the manipulation of the perceptual factors favor the performance the object searching task. Its is discussed the relation of these results with the problem of the AB error.